Loop-shaping H[the sign of infinity] control of an aeropendulum model - Breganon, Ricardo; Alves, Uiliam Nelson LT; De Almeida, Joao Paulo LS; Ribeiro, Fernando SF; Mendonça, Marcio; Palácios, Rodrigo HC; Montezuma, Marcio AF (Zielona Góra: Uniwersytet Zielonogórski)
Inverted pendulum systems present high dynamic complexity and represent a challenge in the automatic control field due to their nonlinearity and unstable equilibrium point when the pendulum rod is at the vertical position.
Keywords: dynamic system modeling; aeropendulum; H[the sign of infinity] control